2019
DOI: 10.1139/bcb-2018-0231
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of the small heat-shock protein p26 by RNA interference modifies the diapause proteome ofArtemia franciscana

Abstract: Embryos of the crustacean Artemia franciscana may arrest as gastrulae, forming cysts that enter diapause, which is a state of reduced metabolism and enhanced stress tolerance. Diapausing cysts survive physiological stresses for years due, in part, to molecular chaperones. p26, a small heat-shock protein, is an abundant diapause-specific molecular chaperone in cysts, and it affects embryo development and stress tolerance. p26 is therefore thought to influence many proteins in cysts, and this study was undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This sugar forms H bonds with proteins and phospholipids, forming a kind of bioglass, in a process called vitrification, allowing the maintenance of internal stability. 54,60,[67][68][69][70][71][72][73] Besides this first adaptative level of hatching reduction, another deeper level of hatching inhibition was revealed after the analysis of the whole population, independent of time and moon phase, with high statistical significance and large effect size against the controls, as observed after treatment with MC 30cH (►Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…This sugar forms H bonds with proteins and phospholipids, forming a kind of bioglass, in a process called vitrification, allowing the maintenance of internal stability. 54,60,[67][68][69][70][71][72][73] Besides this first adaptative level of hatching reduction, another deeper level of hatching inhibition was revealed after the analysis of the whole population, independent of time and moon phase, with high statistical significance and large effect size against the controls, as observed after treatment with MC 30cH (►Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…HSPB7, located on 1p36.13, is a member of heat shock protein (HSP) family that plays essential roles in protein folding and cellular protein homeostasis [26]. Heat shock proteins have been implicated in diverse range of cellular processes, such as stress response, cell proliferation, and apoptosis [27][28][29]. Recent studies have revealed that heat shock proteins also play crucial roles in osteogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was necessary to investigate the mechanisms involved through gene expression of HSPs, which actively participate in bioresilience processes in the genus Artemia. [11][12][13][14][15][60][61][62][63] Compared to the other treatments, an increase in Hsp26 and p26 gene expression was seen in cysts and nauplii treated with Isotherapic (R. raciborskii extract) 200cH. The protein p26 is a small HSP that is abundant in A. franciscana embryos during diapause.…”
Section: Discussionmentioning
confidence: 99%